التصور الفكري التربوي الأخلاقي في تطوير المجتمع: دراسة تحليلية من منظور القرآن الكريم = The intellectual, educational and behavorial worldview in societal development: an analytical study from the Qur'anic perspective - Yaakob, Faridah; Muhammad, Fatimah; Mohammed Yaqub, Mohammed Abullais Shamsuddin (Department of Usuluddin and Comparative Religion, Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University of Malaysia, 2019)
This study analyzes the worldview of intellectual, educational and behavorial aspects of societal development from the Qur‘anic perpective. It utilizes the deductional method by collecting views of the Muslim scholars in explaining Qur‘anic verses and Aḥadith related to this topic, and subsequently the analytical method in analyzing those opinions. This research results in identification of the crisis facing the Muslim Ummah of today‘s world which are: firstly, the lack of structured intellectual, educational and behavorial worldview. Secondly, the lack of its strategic development due to blind imitation of the West in variety of fields and finally, the lack of virtues such as truthfulness, integrity, justice and patience among Muslims. This study discovers methods to solve this crisis from the Qur‘anic perspective through implementation of its intellectual, religious, spiritual and behavorial principals. ********************************************************************************* قام هذا البحث بدراسة وتحليل التصور الفكري التربوي الأخلاقي في تطوير المجتمع من منظور القرآن الكريم. واعتمد البحث على المنهج الاستقرائي لجمع أقوال العلماء في بيان الآيات القرآنية والأحاديث المتعلقة بالموضوع، والمنهج التحليلي لتحليل تلك الأقوال. ومن أهم نتائج البحث: أن من الأزمات التي تلبست بها الأمة في وقتنا الحاضر: غياب الفكر التربوي الأخلاقي المنظم في تطوير المجتمع عن خواطر أبنائها، وغياب الاستراتيجية المؤثرة في تنظيمه عن وعيهم مما ينجم عنه تقليدهم الأعمى للفكرة الغربية في مختلف المجالات، وابتعادهم عن ممارسة الأخلاق النبيلة كالصدق والأمانة والعدل والصبر. واكتشف البحث كيفية معالجة هذا الإشكال في القرآن الكريم، فوجدها ممثلة في غرس الأسس الفكرية العقدية، والتعبدية، والأخلاقية.